Parent perspectives on school food allergy policy - S. Shahzad Mustafa; Anne F. Russell; Olga Kagan; Lauren M. Kao; Diane V. Houdek; Bridget M. Smith; Julie Wang; Ruchi S. Gupta (BMC, 2018)
Abstract Background Food allergy affects up to 8% of children in the U.S. There is minimal research to date on food allergy policies that are currently in place in schools and the opinions of parents of children with food allergy on the effectiveness of or need for these policies. Methods An electronic survey was disseminated to parents of children with food allergy. Frequencies were calculated to describe respondent characteristics and responses. Chi-square tests were performed to examine associations between school and child characteristics and outcomes. Results Of the 289 parent respondents, 27.4% were unsure or felt school was unsafe for their child with food allergy. While the majority felt that the polices in their child's school were helpful, most also believed that implementation of additional polices was necessary, including availability of stock epinephrine (94.2%), lunch menus with allergen information (86%), ingredient labels on food items (81%), and direct food allergy education for students (86%). There were significant differences in school food allergy policy depending on the age of the student body, private versus public school, and geographic location. Conclusions While most schools reportedly have one or more food allergy policies in place, many parents have concerns over the safety of their child at school and feel that additional policies are necessary to improve the safety of the school environment for children with food allergy. The availability of stock epinephrine, improved allergen labeling of food and menus and increased food allergy education may be key policy areas on which to focus.